2008
DOI: 10.1007/s10071-008-0191-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatial learning in pigs: effects of environmental enrichment and individual characteristics on behaviour and performance

Abstract: This study investigated the eVects of both environmental enrichment and individual behavioural characteristics on spatial cognitive capabilities of pigs, using a novel latent spatial learning paradigm based on Tolman's detour experiments (1948). Pigs were housed either in 'barren' pens or in pens enriched with straw bedding from birth. Pigs were restrained in a Backtest at 10 and 17 days postpartum. Based on their escape behaviour in this test, which has been shown to reXect their behavioural style, six 'high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
2
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 63 publications
1
32
2
5
Order By: Relevance
“…Another personality trait that may contribute to the tendency of animals to develop aberrant behaviours is fearfulness or anxiety [19], [20] which may be reflected in the response to novel situations [21], [22]. Additionally, in pigs the behaviour in novelty tests has been associated with coping styles [23], tail biting [20], and serotonergic blood and brain parameters [22]. Therefore, the main aim of our study was to explore whether tail biting in pigs, in a longitudinal study, is associated with behavioural and physiological responses to challenges, and also with blood serotonin.…”
Section: Introductionmentioning
confidence: 99%
“…Another personality trait that may contribute to the tendency of animals to develop aberrant behaviours is fearfulness or anxiety [19], [20] which may be reflected in the response to novel situations [21], [22]. Additionally, in pigs the behaviour in novelty tests has been associated with coping styles [23], tail biting [20], and serotonergic blood and brain parameters [22]. Therefore, the main aim of our study was to explore whether tail biting in pigs, in a longitudinal study, is associated with behavioural and physiological responses to challenges, and also with blood serotonin.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Although EE research has been mostly focused on rodents, similar effects have been reported in several species of mammals (gerbils, ground squirrels, rabbits, cats and primates). [28][29][30][31][32] …”
mentioning
confidence: 99%
“…2008). And perhaps not surprisingly, researchers have concluded that pigs are good problem‐solvers (Wood‐Gush and Vestergaard 1991; Jansen et al. 2009).…”
Section: Animal Science: Understanding Subjectivity Through Mental Camentioning
confidence: 99%